Mm-wave generation using unbalanced Mach- Zehnder modulator and optical frequency comb source for DWDM optical network - Eltaif, Tawfig; Alaghbari, Khaled; Alsowaidi, Naif; Hamida, Belal Ahmed (Institute of Electrical and Electronics Engineers Inc., 2021)
this paper demonstrating a successful photonics generation of 60GHz millimeter-wave by quadrupling a 15GHz RF signal with an unbalanced Mach-Zehnder modulator (UMZM). With a 4ps delay between the two arms of UMZM and by controlling the modulation index of UMZM, only two side bands can be generated along with the main carrier, which is suppressed by a band pass filter. Hence, a millimeter-wave of 60GHz is generated with a total suppression of undesired low/high-order harmonics. Moreover, an optical comb with spacing of 30GHz is generated using a cascade of intensity and phase modulators and utilized for an optical wavelength-division multiplexing (WDM) transmission system at data rate of 5Gbps for each user. Results show that the system maintains good bit error rate performance up to a receiver sensitivity of -22dBm